Strengthening Early Childhood and Primary Teacher Capacity for Digital-Age Teaching: A Community-Service Professional Development Study - Novela Juliana (CV. TOTUS TUUS, 2025)
Schools increasingly expect teachers to orchestrate meaningful digital learning, yet many ECE/primary contexts still face gaps in skills, tools, and parent–school coordination; against this backdrop, the present community-service professional development (PD) program aimed to strengthen teacher capacity for adaptive, technology-enhanced instruction and ethical digital use. The intervention combined an interactive seminar–workshop with structured mentoring and involved 23 teachers, with outcomes assessed through pre/post knowledge tests, a five-dimension performance rubric applied to lesson and assessment artifacts, classroom observations of student engagement, and surveys capturing satisfaction and intent to use. Results indicated marked gains in teachers’ digital knowledge and self-efficacy; concurrent improvements appeared in the clarity of goals, constructive alignment, and rubric quality within submitted artifacts, while classrooms showed early adoption of low-barrier digital practices—such as quizzes, polls, and rapid feedback—accompanied by higher student participation. Higher-demand innovations (e.g., authentic projects, short micro-videos, and parent digital-citizenship guidelines) began to emerge but required continued support to embed sustainably. Overall, the findings suggest that practice-proximal PD—pairing concrete models/templates with guided production and iterative feedback—can quickly elevate foundational digital-pedagogical capacity in ECE/primary settings. The program offers a replicable pathway for schools to scaffold SAMR-progression, embed assessment-as-learning routines, and co-construct digital citizenship with families. Future service should extend the model with additional coaching cycles, parent workshops focused on active mediation, simple dashboards to track adoption and feedback timeliness, and longer follow-up windows to evaluate sustained classroom change.